Structural characterization of stalk lignin from banana plant - Oliveira, L.
Dioxane lignins from two fractions of banana plant 'Dwarf Cavendish' stalk (floral stalk (DL(FS)) and rachis (DL(R))) were structurally characterized by a set of spectroscopic (Ultraviolet (UV), FTIR, solid- and liquid-state NMR) and chemical degradation (permanganate (PC) and nitrobenzene oxidation (NO)) techniques. Despite both lignins are of HGS-type, strong structural differences were observed between them. Thus, DL(FS) showed almost twice the abundance of H and G units and almost half of the abundance of S units when compared to DLR. DLR possessed significantly higher amount of beta-O-4' structures (0.32/C(6) against 0.12/C(6)) and the molecular weight (5400 Da against 3750 Da) than those of DL(FS). About 72% of the condensed structures in DL(FS) are of beta-5 and 5-5' types, whereas 4-O-5'-diaryl ether structures were the most abundant condensed structures in DL(R). Most of H units in both lignins are terminal phenolic coumarates linked to lignin substructures by ester bonds. Both lignins are structurally associated with suberin-like components in cell wall tissues. Structural features of stalk lignin were discussed in terms of possible restrictions for the kraft pulping of integral stem material. (C) 2008 Elsevier B.V. All rights reserved.